Pemanfaatan Karbon Aktif Kulit Pisang Kepok dan Karbon Aktif Tempurung Nipah sebagai Biosorben untuk Pengolahan Limbah Cair Laundry - Ilma Fadlilah; Ayu Pramita; Nurlinda Ayu Triwuri; Heni Anggorowati (Eksergi, 2023)
The use of kepok banana peel activated carbon (AC-KPK) and nipa shell activated carbon (AC-TN) to adsorb phosphate ions in laundry waste has been successfully carried out. Characterization of activated carbon was carried out with SEM-EDX. The results of the morphological analysis showed that the pore sizes in AC-KPK and AC-TN were included in the macropore category. The elemental content of the AC-KPK adsorbent is C 74.9%; 23.6% O and 1.5% K, whereas in the AC-TN adsorbent it was observed that C elements were 70.7%; O 25.5%; K 2.0% and other elements such as Ca, Na, Mg and Cl are contained in small quantities. The optimum contact time needed by AC-KPK to adsorb phosphate ions in laundry wastewater is 15 minutes with an adsorption efficiency of 98.83%, the AC-TN adsorbent is 5 minutes with an adsorption efficiency of 99.52%, and the combination of AC-KPK&AC- TN resulted in a contact time of 5 minutes with an adsorption efficiency of 99.91%. The adsorption kinetics of phosphate ions with the three adsorbent media followed the pseudo second order model with adsorption rates for the adsorbents AC-KPK, AC-TN, and the combination AC-KPK & AC-TN respectively 3.9400 g/mg.min; -28.7119 g/mg.minute; and -10.8895 g/mg.min.